Evaluation of the impact of freezing preparation techniques on the characterisation of alginate hydrogels by cryo-SEM. (September 2016) - Aston, Robyn; Sewell, Kim; Klein, Travis; Lawrie, Gwen; Grøndahl, Lisbeth
Graphical abstract: Highlights: New insights into the structure of hydrogels. Examples of artefacts observed in Cryo-SEM images. Recommendations for minimum methodological information for reporting Cryo-SEM experiments. Abstract: The structural characterisation of high water content materials such as hydrogels is challenging due to the inherent properties of water that are dependent on conditions of temperature and pressure. Cryo-scanning electron microscopy (cryo-SEM) has potential to offer the most authentic insights into the native structure of polysaccharide hydrogels, due to the ability to freeze the sample under conditions where transparent vitreous ice is formed. The advantages, challenges and constraints of cryo-SEM in characterising the porous matrix of alginate hydrogels are considered in this tutorial paper through examples from our own studies. Recommendations are proposed for the minimum methodological information that is required from researchers as part of the publication of their studies of hydrogel samples to enable critical appraisal of their cryo-SEM images.